Finite element analysis of end-plate connection under seismic loading - Fong, Khai Yeh (2012)
The bolted end-plate connection was chosen as an important type of beamcolumn connections for its complexity in the analysis and behaviour due to the amount of connection element and their inheritable non-linear behaviour. A great deal of experiments and earthquake disasters have shown that semi-rigid composite connections have excellent mechanical and seismic performance. In practical engineering field, the using of semi-rigid composite connections can reduce steel consumption and accelerate construction process. This study attempts to analyze the behavior of the bolt end-plate connection under seismic loading by using finite element method. Comparison between the flush and extended end-plate connections with or without stiffeners is made to predict the strength and stability of the end-plate connection. Previous research shows that typical end-plate connection extended on both sides can provide the strength, joint rotational stiffness, ductility and energy dissipation capacity required for use in seismic moment steel frames. LUSAS 14.0 program used to analysis the eight models in this project. The dimensions of columns are 250x300x2200 mm; beam is 200x300x1200 mm; end-plate stiffener lOOxlOOxlOmm and column flange stiffener 120x300x12 mm respectively. Linear analysis is performed to determine the deformed, maximum stress and strain under the cyclic load condition. In addition, another two analyses are also conducted to obtain deformed mesh by eigenvalue frequency analysis and motion parameter by seismic analysis. Based on the test results and analysis, end-plate connection was stiffened eithers at column flange or end plate shows higher stability and resistance to seismic loading compare to without stiffeners. It concludes that end-plate connection can provide better strength and energy dissipation compare to flush end-plate connection which required for moment resistant connection in earthquake region. Various parameter geometric of end-plate connection is recommended for further investigate.